Perception of Young People about their Expectations for the Future in Four Educational Institutions of the Municipality of Soacha (Cundinamarca, Colombia) (2020)
This article gathers the investigative exercise from a descriptive quantitative approach about the analysis of the perception of the humanistic area with emphasis on the life project of three educational institutions in the municipality of Soacha (Cundinamarca, Colombia). Data collection is carried out through the EFFA instrument (Scale of Expectations for the Future of Adolescence) with the aim of identifying the perception of the students of the four basic and middle educational institutions about their projection of life in the medium term. The EFFA instrument was designed and validated in three previous investigations (Sánchez Sandoval y Verdugo, 2016) and later adapted before its application in this investigation. As a result of this research, it was evidenced that higher future expectations by adolescents produce an increase in their self-esteem, which is not only reflected in their self-concept but in the quality of their interpersonal relationships and their ability to bond with society, too. All of this, allows that young people with higher expectations for the future, take better advantage of the opportunities offered by the environment to improve their quality of life, even in cases in which social mobility channels are not accessed through admission to third level educational institutions.